MADRASAH ALIYAH (ISLAMIC SENIOR HIGH SCHOOL)TEACHER PERFORMANCE MANAGEMENT IN PRINGSEWU REGENCY, LAMPUNG PROVINCE, INDONESIA - almursyid, adhar; koderi, koderi (Universitas Pendidikan Indonesia, 2020)
This study aims to describe the madrasah aliyah teacher performance management in Pringsewu regency by covering the process of human resources planning, performance coaching, and performance assessment. The approach used was qualitative-descriptive. The data was collected through observation, interviews, and documentation. The data was then analyzed through data presentation, data reduction, and conclusion drawing. The results showed that the performance management process carried out by madrasah aliyah in Pringsewu are human resources planning, performance coaching, and performance assessment. However, there are differences in the implementation of the process due to several factors such as the status of the schools and the level of development. The human resource planning in the madrasah already included the analysis of teachers’ needs, teacher development through academic supervision activities, workshops or training activities through MGMP, career development, compensation, sanction, and granting further education permits. The fundamental difference between madrasah is that the civil servant teachers have better career development, compensation, and salary compared to the teachers in private schools. However, the performance management process activities have not been carried out systematically, varied, and simultaneously so that in the future, it is expected to be improved.Keywords: Management, Performance, Resources, Teachers